Some further vertex turán numbers for cube graphs - Harborth, Heiko; Nienborg, Hauke (Utilitas Mathematica, 2008)
Partial results are obtained for the minimum number h(n, k) of vertices to be deleted from the cube graph Qn such that no subgraph Qk is complete.